2019
DOI: 10.1108/ijced-05-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Mixed implications of private supplementary tutoring for students’ learning

Abstract: Purpose Private supplementary tutoring, common in many countries, has mixed (both positive and negative) dimensions that impact student learning. Private supplementary tutoring runs parallel to mainstream schooling and provides lessons before or after school hours in exchange for additional fees. The purpose of this paper is to focus on how private supplementary tutoring benefits students’ learning in secondary education. It also identifies the drawbacks of tutoring, and shows variations in and between urban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Participants in this study were aware of this situation, and some spoke about it and asserted their understandings that PT-E would be responsible for deterioration of the education as a whole in Bangladesh. Therefore , Mahmud, (2019), in a study, concluded PT-E tutors did not pay much attention to their classroom practice, could not interested to creating good interaction with students, and sometimes could not complete syllabus within the academic year. Similarly, studies including De Silva (2015) and Zhan et al (2013) reported negative effects private tutoring on the students' education, but the present study goes further to report that private tutoring is not only damaging but also unfair for all disadvantaged learners in terms of equality of opportunities in education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants in this study were aware of this situation, and some spoke about it and asserted their understandings that PT-E would be responsible for deterioration of the education as a whole in Bangladesh. Therefore , Mahmud, (2019), in a study, concluded PT-E tutors did not pay much attention to their classroom practice, could not interested to creating good interaction with students, and sometimes could not complete syllabus within the academic year. Similarly, studies including De Silva (2015) and Zhan et al (2013) reported negative effects private tutoring on the students' education, but the present study goes further to report that private tutoring is not only damaging but also unfair for all disadvantaged learners in terms of equality of opportunities in education.…”
Section: Discussionmentioning
confidence: 99%
“…Education is a crucial sector, and the delivery of good education is very critical for the development of this developing nation. Unfortunately, very little literature is currently available (see e.g., Nath, 2008;Hamid et al, 2009;Mahmud, 2019;Mahmud & Bray, 2017) that examines English teaching-learning beyond the formal school classroom and their dynamics in the urban and rural part of Bangladesh. The Bangladeshi people have been shifting to coaching centre business through the government ban on private tuition by the schoolteachers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, ASER data analyses for Pakistan and India find that private tuition improves learning outcomes more in poorer children than richer children, narrowing some of the wealth disparity in learning (Alcott and Rose 2015). Mixed methods analysis on the effects of private tutoring in Bangladesh finds that there are positive effects on learning attainment and test preparation, but it increases teaching to the test (Mahmud 2019).…”
Section: Demand For Private Schooling and Tutoringmentioning
confidence: 99%